Is early childhood education associated with better midlife cognition, especially for children facing socioeconomic marginalization? - Whitney Wells; Jillian Hebert; Chloe W. Eng; Catherine dP. Duarte; Anusha M. Vable (PLoS ONE, 2026)
Purpose Education is a strong predictor of cognitive aging, but little work has evaluated the relationship between early childhood education (ECE) specifically and cognition in midlife and beyond. Methods Using data from the National Longitudinal Survey of Youth 1979 Cohort (n = 7,129), we examined the relationship between attending preschool, Head Start (federally-funded free ECE targeted for low-income families), or no ECE, and midlife global cognition. We defined midlife global cognition based on immediate and delayed word recall, serial 7 subtraction, and backwards counting. We used multivariable linear regression models to estimate overall associations and associations among groups more likely eligible for Head Start, and to evaluate heterogeneities by sex, race and ethnicity, and family socioeconomic status (SES). Results Overall, preschool, but not Head Start, was associated with better midlife cognition compared to no ECE in some models. Among families more likely eligible for Head Start, we found not only that preschool (β = 0.26; 95% CI: 0.01, 0.51) was associated with better midlife cognition, but also directionally positive evidence that Head Start (β = 0.09; 95% CI: −0.08, 0.27) was associated with better midlife cognition. Associations varied; Head Start was associated with higher midlife cognition for Black and Hispanic men and people with higher family SES marginalization compared to other groups. Conclusions This study provides initial evidence suggesting that early childhood education may be associated with better cognition more than 40 years later, especially for Black and Hispanic men and people who faced greater socioeconomic marginalization.